Co–N-doped single-crystal V3S4 nanoparticles as pH-universal electrocatalysts for enhanced hydrogen evolution reaction. (1st March 2020) - Cao, Liyun; Wang, Linlin; Feng, Liangliang; Kim, Jae-hyun; Du, Yingying; Yang, Dan; Kou, Lingjiang; Huang, Jianfeng
Abstract: The exploitation of innovative and high-efficiency inexpensive electrocatalysts for hydrogen evolution reaction (HER) over a wide pH range is highly pivotal but still challenging. Herein, a simple one-step vacuum pyrolysis approach without using H2 S is reported to synthesize Co–N-doped single-crystal V3 S4 nanoparticles (Co–N–V3 S4 ), which can function as highly active and stable nonprecious electrocatalysts toward HER at all pH values (pH 0–14). Furthermore, we demonstrate that the use of trithiocyanuric acid as both nitrogen and sulfur sources along with Co-precursor can not only trigger the incorporation of highly active Co–N sites and the high-content N doping, but also well modulate its electronic structure and thus the improved electrocatalytic HER activity. Results show that the as-obtained Co–N–V3 S4 material needs small overpotentials of 268 mV, 260 mV and 252 mV at the current density of 10 mA cm −2 in acid (pH 0), neutral (pH 7) and alkaline (pH 14) solutions, respectively, and offers a durable catalytic stability for at least 10 h, as well as gives a Faradaic yield close to 100% at all pH values. Our findings of identifying V3 S4 as the catalytically active vanadium sulfide phase for HER and developing a metal-doping induced structure-regulating strategy for the enhancement of catalytic performance broaden our horizons and meanwhile provide fresh insights to rationally design highly efficient noble-metal-free electrocatalysts toward water splitting. Graphical abstract: A simple one-step vacuum pyrolysis approach is developed to synthesize Co–N-doped single-crystal V3 S4 nanoparticles which are proven to be a highly active and pH-universal electrocatalyst for hydrogen evolution. Image 1